Pengaruh Pendidikan Anti Korupsi Terhadap Kesadaran Serta Keterampilan Kritis Peserta Didik Di MTsN Makassar - Bagus Mastory; Muhammad Syukur; Najamuddin Najamuddin; Syamsu A Kamaruddin; Andi Octamaya Tenri Awaru; Romansyah Sahabuddin (Universitas Negeri Malang, 2025)
Abstract: This research is motivated by the urgency of eradicating corruption in Indonesia through preventive educational channels, particularly in the effort to deconstruct the residue of